1969
DOI: 10.4095/104706
|View full text |Cite
|
Sign up to set email alerts
|

Kluane Lake, Yukon Territory, Its Drainage and Allied Problems

Abstract: Changes of level of Kluane Lake suggest that the lake has not always drained through the Kluane River as it does today but has, during the Hypsithermal, drained through the Slims River valley into the Kaskawulsh River. This drainage theory was first published by the writer in 1952 and the present paper includes data which has become available since that time. Features of change of level as well as possibilities of drainage reversal are here discussed and it remains the writer's conclusion that the drainage cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Kluane Lake, situated in the southwest Yukon Territory in Canada, is now part of the Yukon River drainage. However, Bostock (1969) suggested that Kluane Lake used to be part of the Alsek River drainage until the advance of the Kaskawulsh glacier about 400 years ago. (The Alsek River populations, while distinct, were more similar to Russian populations than they were to present-day upper Yukon River populations.…”
Section: Discussionmentioning
confidence: 99%
“…Kluane Lake, situated in the southwest Yukon Territory in Canada, is now part of the Yukon River drainage. However, Bostock (1969) suggested that Kluane Lake used to be part of the Alsek River drainage until the advance of the Kaskawulsh glacier about 400 years ago. (The Alsek River populations, while distinct, were more similar to Russian populations than they were to present-day upper Yukon River populations.…”
Section: Discussionmentioning
confidence: 99%
“…Lake sediments can also be used to study past seismic activity (Doig, 1998) or water-level variations. Buried tree stumps in several areas of Kluane Lake attest to recent major changes in the water level (Bostock, 1969), and a study of Kluane Lake (Clague et al, 2006;Brahney et al, 2008) showed that glacier fluctuations have important effects on the location and altitude of the outlet, and thereby, on the water level. The White River Ash event (Bunbury and Gajewski, 2009b) had a stronger effect on aquatic communities at sites nearer to its source, with impacts lasting several decades (Bunbury, 2009;Bunbury and Gajewski, 2013).…”
Section: Other Paleoecological Studiesmentioning
confidence: 99%
“…The Icefield Ranges form a continental drainage divide, but this is a geologically very recent and possibly temporary development (Tempelman-Kluit, 1980; see also Bryan, 1972), and a number of rivers with headwaters in the continental interior penetrate this substantial but discontinuous topographic barrier to empty into the Pacific. One of the study rivers (Kluane; see below) may have reversed flow directions and switched continental drainages in the recent postglacial Holocene (Bostock, 1969), and at least two of the study rivers (Dezadeash and Alsek) have experienced substantial, repeated drainage obstructions due to periodic surges of the Lowell Glacier, which formed large glacier-dammed lakes within these catchments; the most recent full blockage may have occurred around 1900 (Clague and Rampton, 1982). In addition, the terminus of the Kaskawulsh Glacier overlies a continental drainage divide, and the relative volumes of Kaskawulsh meltwater ultimately routed to the Kluane versus Alsek Rivers has been hypothesized to fluctuate from year to year (Bryan, 1972;Barnett, 1974;Johnson, 1986).…”
Section: Study Areamentioning
confidence: 99%